KAJIAN HUTAN KEMASYARAKATAN SEBAGAI SUMBER PENDAPATAN : KASUS DI KAB. GUNUNG KIDUL - Raden Mohammad Mulyadin; Surati Surati; Kuncoro Ariawan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Community forest (HKm) is a state forest that its utilization specifically for empowering communities around forest areas. Community involvement in forest management is strongly needed to maintain forest sustainability and to achieve community welfare. The study aims to assess activities conducted by the HKm that can be a source of  income for forest communities in Gunungkidul district, DI Yogyakarta.  Two forest farmer groups (KTH) were chosen as an example of  research and as many as 40 farmers as respondents. Collecting data using interview techniques, observation and literature study, was analyzed by using quantitative and descriptive qualitative. The quantitative analysis consisted of  household income, balance of  receipts and cost analysis. The results showed that HKm activities can increase the income of  KTH between 20–50%. Activities that can be used as a source of  income consists of  the institutional and HKm management intercropped. Intercropping activities by taking into account composition of  the main crop in the sidelines of  the plant will affect in income levels. The income level of  KTH Tani Manunggal greater than KTH Sedyo Lestari, due to differences in the composition between the main crop and plant sidelines, the amount of  HKm, and the number of  KTH members.